E-Commerce Web Application Untuk Membantu Masyarakat - palit, juliana; Satria, Rizky Adi; Tantowi, Ahmad Ahyani (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Technological developments are currently developing very rapidly and can be utilized by business people. Using the right technology can improve performance in a company. Processes in the business sector are long, complicated and require a long time to become more efficient and reduce costs. E-commerce is a technology that can be applied to a company. E-commerce as an answer to the demands of globalization. With the number of internet users growing rapidly, this is the reason companies implement e-commerce. The development of e-commerce users in Indonesia is currently increasing due to the Covid-19 pandemic and Omicron has become an alternative for carrying out transactions between buyers and sellers to stabilize the economy. In implementing e-commerce to help people sell their products through an e-commerce website.Keywords—E-commerce; sistem informasi; jual-beli; produk; website